PERFORMANCE EFFICIENCY OF SELECTED PHILIPPINES FOOD AND BEVERAGE MANUFACTURING COMPANIES - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
The purpose of this paper is to evaluate and measure the efficiency performance of selected Philippines food and beverage manufacturing companies covering from 2005 to 2007. Two input and output variables of five companies listed in the Philippine Stock Exchange were examined using Data Envelopment Analysis (DEA) model to evaluate the companies’ performance. The results generally indicate that too much capital use and high operating expenses in conjunction with low revenue or sales characterize inefficient operations. The result suggests that the companies with the presence of slack must evaluate especially the idle capital, inefficient use of operating expenses and concentrate on increasing the total sales. DEA approach is able to determine the benchmarking company among other Philippines food and beverage manufacturing companies.